Microforce Sensing and Flexible Assembly Method for Key Parts of ICF Microtargets - Chen, Tao; Ni, Kejian; Zhu, Minglu; Sun, Lining (Actuators, 2023)
Microassembly is one of the key techniques in various advanced industrial applications. Meanwhile, high success rates for axial hole assembly of thin-walled deep-cavity-type items remain a challenging issue. Hence, the flexible assembly approach of thin-walled deep-cavity parts is investigated in this study using the assembly of the key components, the microtarget component TMP (thermomechanical package) and the hohlraum in ICF (inertial confinement fusion) research, as examples. A clamping force-assembly force mapping model based on multisource microforce sensors was developed to overcome the incapacity of microscopic vision to properly identify the condition of components after contact. The ICF microtarget flexible assembly system, which integrates multisource microforce sensing and a six degrees of freedom micromotion sliding table, is presented to address the constraint that the standard microassembly approach is difficult to operate once the parts contact. This method can detect contact force down to the mN level, modify deviation of the component posture efficiently, and achieve nondestructive ICF microtarget assembly at the end.